Evaluation of the Effects of Charged Amino Acids on Uncontrolled Seizures - Hossein Ali Ebrahimi; Saeed Ebrahimi (Neurology Research International)
Introduction. Epilepsy is one of the most common diseases of the central nervous system. The prevalence of epilepsy throughout the world is 0.5 to 1%, and the same rate is 7.8 per 1000 in Kerman. Almost 20 to 30% of epileptic patients do not respond properly to common medications. The present study investigated patients who did not respond to common and, even in some cases, adjuvant therapies, with two seizures or more per week, regardless of the type of the inflicted epilepsy. Methodology. The participants of the present double-blind study were randomly selected into three 10-member groups of uncontrolled epileptic patients (arginine, glutamic acid, and lysine). The patients used amino acid powder dissolved in water (three times the daily need) every day for two weeks before breakfast. The number of seizures was recorded one week prior to commencing amino acid use, as well as the first and the second weeks subsequent to use. Results. A total of 32 patients were studied in three groups. The decline rates of seizures were 53%, 41%, and 13%, and the P value was 0.013, 0.027, and 0.720, respectively. Conclusion. Administration of the charged amino acids, arginine, and glutamic acid can decrease the seizures of patients suffering from uncontrolled epilepsy.